Slow light in photonic crystals waveguides - G. López-Galmiche (Acta Universitaria, 2013)
We analyzed the scattering produced by technological imperfections in a strip photonic crystal waveguide. Modeling and losses analysis of the slow light structures were carried out by plane wave expansion method using the MPB software.